Pertumbuhan Mikroalga Chlamydomonas dalam Medium Beneck dan Air Tanah yang Mengandung Insektisida Berbahan Aktif Klorpirifos - M. Kurniasih; N. B. Prihantini; E. Nurtiyani (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
The research of insecticide effect to the growth of genus Chlamydomonas had been done.  Research was experimental study with block random design to 9 concentrations of chlorpiriphos containing insecticide in Beneck and soil water media i.e. 0 (control), 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, and 0.40%.  Observations were done for 35 days.  Friedman test showed that there were some effects of media and insecticide concentrations on cell numbers of Chlamydomonas (cell/ml) in culture (p>0.05).  Dunnets test showed that mean of cell numbers of Chlamydomonas (cell/ml) differ (on p>0.05) and very differ (on p>0.01) on every concentrations in Beneck and soil water media.  Insecticide could reduced the cell size of Chlamydomonas, yet increased the number of cells on 0.05--0.30% concentrations in Beneck medium, and 0.05--0.20% concentrations in soil water medium.  On peak culture, insecticide with 0.10% concentration produced the highest cell numbers i.e. 21,179,167 cell/ml in Beneck medium, and 4,087,500 cell/ml in soil water medium.